Spatiality of Local Governments in European Intermediate Urban Regions: A Methodological Approach - Breuer, Christophe; Halleux, Jean-Marie (Quaestiones Geographicae, 2016)
Local authorities are central actors in the governance of European intermediate urban regions. In this paper, we propose a methodology to analyse the fragmentation of local authorities within 119 urban regions. We tested several European databases to create indicators of fragmentation and to develop a typology of fragmentation within cities. Our results show that the Eurostat Cities programme gives a consistent spatial definition of urban regions and that their fragmentation is mainly influenced by national contexts. The developed methodology is a contribution to the debate on territorial reforms and urban governance transformations.